From dry-land to the water: training and testing practices of strength and conditioning coaches in high level French sprint swimmers - Raineteau, Yannis; Pla, Robin; Bideau, Benoit; Bideau, Nicolas; Nicolas, Guillaume (Frontiers in Sports and Active Living, 2024)
Introduction The aim of this study was to explore training and testing practices from Strength & Conditioning (S&C) coaches who manage groups of high-level French swimmers in elite training centers. The transfer of abilities from dry-land to in situ condition was also investigated. Methods 24 French S&C coaches completed a survey via an online platform. Frequency analyses were made for quantitative and qualitative responses, the level of significance set for this study was p ≤ 0.05. Results Core stability, Strength & Power were the three most targeted qualities. Core strengthening in all its forms, Bench Press & Squat were the three most prescribed exercises. 79% of S&C coaches adapted exercises according to different parameters. Most of the coaches indicated that dry-land S&C sessions were preferentially placed before in-water sessions. Very varied exercises were used in-water to make the transfer from dry-land more effective. 87% of participants monitored the training load and 38% assessed the force and velocity parameters for some S&C exercises. Discussion Dry-land training practices of S&C coaches were mostly in line with scientific recommendations. In the light of results of the questionnaire, it would appear that testing procedures might be a key issue for transferring qualities from dry-land to in situ.